Advancing the understanding of allergic contact dermatitis: from pathophysiology to novel therapeutic approaches - Tramontana, Marta; Hansel, Katharina; Bianchi, Leonardo; Sensini, Chiara; Malatesta, Nicolò; Stingeni, Luca (Frontiers in Medicine, 2023)
Allergic contact dermatitis (ACD) is a common inflammatory skin disease associated, especially if condition becomes chronic, with a high impact on quality of life and significant disease burden. It represents a type IV delayed-type hypersensitivity triggered by contact with an allergen in previously sensitized subjects through the activation of allergen-specific T cells. In the acute phase, it is characterized by an eczematous dermatitis with erythema, oedema, vesicles, scaling and intense itch, even if non eczematous clinical forms are also described (lichenoid, bullous, lymphomatoid…). Lichenification is the most common clinical picture in the chronic phase, that occurs if the culprit allergen is not found or eliminated. ACD can be associated both with occupational and not occupational exposure to allergens, representing, together with irritant contact dermatitis (ICD), about 90% of occupational skin disorders. Patch testing with suspected allergens is required for the diagnosis. Metals, especially nickel, fragrance mix, isothiazolinones and para-phenylenediamine are the most commonly positive allergen in patients patch tested for suspected ACD. The goal of treatment is the avoidance of the contact with the culprit agent, associated with topical and/or systemic corticosteroid therapy.